As bibliotecas na cibercultura: Crítica da estética da informação na era do cyberspace - Zafalon, Zaira Regina (2006)
The purpose of this Master s Dissertation is to study virtual libraries from a historical and descriptive standpoint, with emphasis on a recurrent conceptual setting within the context of cyberculture, taken as a time category corresponding to the contemporary phase of mediatic civilization. The empirical factors and aspects of the object of research have been delimited since at least 1994. Based on a research methodology founded upon a review of the literature, this work involves a study of traditional, real time and hybrid libraries. The subject of this research, marked by theoretical and practical aspects, encompasses general and specific implications concerning the emergence of virtual libraries, involving, simultaneously, the hypotheses that the emergence of virtual libraries may not show a correlation with traditional libraries and that the development of the former is due to the development of the latter or even to a process motivated by the typicity of the post-modern culture. The attainment of the objectives of this research presupposes an understanding of the social, historical and cultural statute of libraries in general and of the sociotechnological aspects of cyberculture and cyberspace; a study of the influence of postmodern culture on the development or the obliteration, oblivion or pulverization of traditional libraries; identification of the modus operandi of the process of acculturation in cyberspace; and an understanding of the change in the esthetics of information in the cybercultural environment. Similarly, this study aims to analyze the various models of organization of information, focusing on its access, within the ambit of in loco, real time and hybrid libraries, which, in this context, implies a critical survey of the technologies destined for the development of bibliotheconomic services. Based on this demarcation of theoretical and methodological principles, the development and consolidation of the horizons of this Dissertation encompass, fundamentally, its entire belongingness to the area of Communications